Governance of the Sponge City Programme in China with Wuhan as a case study - Dai, Liping; van Rijswick, Helena F. M. W.; Driessen, Peter P. J.; Keessen, Andrea M. (International journal of water resources development, 2018)
In 2015, China's national government initiated a Sponge City Programme to address its urban flood issues. A sponge city is a city built around the concept of managing water in an ecologically sustainable way. The intention is to improve urban resilience through rainwater capture, storage and use. This article applies a four-mode governance framework to analyze the programme. It identifies the strengths and weaknesses of the programme implementation and provides recommendations.